Clotting and chromogenic factor VIII assay variability in post‐infusion and spiked samples containing full‐length recombinant FVIII or recombinant factor VIII Fc fusion protein (rFVIIIFc). (17th December 2018) - Kitchen, Steve; Jennings, Ian; Makris, Mike; Kitchen, Dianne Patricia; Woods, Timothy A. L.; Walker, Isobel D.
Abstract: Introduction: Variability in FVIII measurement is a recognized problem. There are limited data for samples containing recombinant Factor VIII Fc fusion protein (rFVIIIFc). Many studies use samples for which factor concentrate has been spiked into FVIII deficient plasma in vitro. This approach requires validation. Aim/Methods: Four samples were distributed in a UK National External Quality Assessment Scheme for Blood Coagulation (NEQAS BC) survey. One contained Advate (full‐length recombinant FVIII) (rFVIII) added to FVIII deficient plasma, one was from a severe haemophilia A patient after infusion of Advate, one was prepared by addition of rFVIIIFc (marketed as Elocta/Eloctate) to FVIII deficient plasma and the fourth was collected from a severe haemophilia A patient following rFVIIIFc (Eloctate) infusion. Fifty‐three haemophilia centres (UK and Scandinavia) performed one‐stage FVIII assays and 27 performed chromogenic FVIII assays. Results/Conclusions: One‐stage assays gave significantly lower results than chromogenic assays by 7% ( P < 0.01) and 13%( P < 0.001) for post‐Advate and Advate spiked samples, and by 22% ( P < 0.001) and 23% ( P < 0.001) for post‐rFVIIIFc and rFVIIIFc spiked samples. The interlaboratory variation was similar for all samples, with CVs of 12%‐16% (chromogenic) and 10%‐13% (one stage). The data indicate that either product can be safely monitored by one‐stage or chromogenic assay. Spiked samples behaved in a similar way to post‐infusion samples for both products and could be substituted for post‐infusion samples for use in proficiency testing exercises (ie, samples were commutable).